STUDY OF THE ACUTE TOXICITY AND SPECIFIC ACTIVITY OF THE PREPARATION "LORSED" - Jabbarova Shokhista Abdurakhim kizi; Tadjibayev Abdisattor Baxodirovich (Journal Park Publishing, 2025)
Studies have been conducted on the acute toxicity of the "Lorsed" preparation based on the dry extract of astilbe chinensis. It has been experimentally established that the drug, when administered at doses of 3000 mg/kg, does not cause changes in the behavior and functional state of mice and does not cause their death. LD50 of the "Lorsed" drug was > 6664 mg/kg. According to the toxicity classification of substances, the tested drug is classified as low-toxic.